Do social factors influence learning among undergraduate medical students? A cross sectional analytical study - Gorantla, Misha; Thomas, Vimala (International Journal Of Community Medicine And Public Health, 2017)
Background: Student self-assessment occurs when learners make judgments about aspects of their own performance. There are several social, educational, demographic and environmental factors that have a direct bearing on learning. This study helps to identify these. The objectives of this study are to assess student’s ability to cope with academic environment based on their self-evaluation and to study the effect of socio-demographic factors on their academic coping ability. Methods: The present cross section study was done in Gandhi Medical College on all first year MBBS students. It was conducted between1st January to 20th January 2016. A pre designed pre structured self-administered questionnaire was given to all students willing to participate in the study. The responses were analysed to study the influence of social factors on student learning outcomes. The study participants included a total of 179 students. Results: This study found that majority of the students (64.2%) were 18 years old. Most of the students (89%) belonged to urban area; fathers of majority of students (49.2%) were professional degree holders. Majority (97%) students were educated in English medium but majority (70.9%) students communicated with friends in Telugu. A majority of 54% felt that teachers should local language also during lectures to prevent language barrier while learning. Conclusions: We found that students educated in Telugu medium and students with fathers engaged in unskilled occupations showed poorer coping ability with an odds ratio of 9.1 and 3.2 respectively at 95% CI.